The Gambia : Report on the Observance of Standards and Codes; Data Module, Response by the Authorities, and Detailed Assessments Using the Data Quality Assessment Framework. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Report on the Observance of Standards and Codes (ROSC)-Data Module provides an assessment of The Gambia's macroeconomic statistics against the recommendations of the General Data Dissemination System, complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework, July 2003. The assessment reveals that the legal framework for statistical activity in The Gambia is broadly adequate. Further legislative effort is under way to promote greater autonomy or authority of some statistical agencies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet